2013
DOI: 10.1073/pnas.1306072110
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3selectively and reversibly impairs T helper-cell CNS localization

Abstract: Pharmacologic targeting of T helper (T H ) cell trafficking poses an attractive opportunity for amelioration of autoimmune diseases such as multiple sclerosis (MS). MS risk is associated with vitamin D deficiency, and its bioactive form, 1,25-dihydroxyvitamin D3 [1,25(OH) 2 D 3 ], has been shown to prevent experimental autoimmune encephalomyelitis, a mouse model of MS, via an incompletely understood mechanism. Herein, we systematically examined 1,25 (OH) 2 D 3 effects on T H cells during their migration fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 39 publications
0
29
0
3
Order By: Relevance
“…However, in this disease model, CD4 + T cells are likely the prime 1,25(OH) 2 D 3 target cells, since other studies show that in this model CD8 + T cells are dispensable for the effects of 1,25(OH) 2 D 3 (174). Further strengthening the hypothesis that the suppression of EAE by 1,25(OH) 2 D 3 is driven by modulation of CD4 + T cells, is the finding that 1,25(OH) 2 D 3 prevents CD4 + Th cell migration into the CNS (175). Finally, VDR binding is enriched near SNPs associated with autoimmune diseases in human CD4 + T cells, suggesting that these cells are also important in the effects of 1,25(OH) 2 D 3 in human autoimmunity (8).…”
Section: Immune Modulation By Vitamin Dmentioning
confidence: 76%
“…However, in this disease model, CD4 + T cells are likely the prime 1,25(OH) 2 D 3 target cells, since other studies show that in this model CD8 + T cells are dispensable for the effects of 1,25(OH) 2 D 3 (174). Further strengthening the hypothesis that the suppression of EAE by 1,25(OH) 2 D 3 is driven by modulation of CD4 + T cells, is the finding that 1,25(OH) 2 D 3 prevents CD4 + Th cell migration into the CNS (175). Finally, VDR binding is enriched near SNPs associated with autoimmune diseases in human CD4 + T cells, suggesting that these cells are also important in the effects of 1,25(OH) 2 D 3 in human autoimmunity (8).…”
Section: Immune Modulation By Vitamin Dmentioning
confidence: 76%
“…[1] In addition, Vitamin D insufficiency has been linked to autoimmune disorders including autoimmune encephalomyelitis, rheumatoid arthritis (RA), systemic lupus erythematosus, type 1 diabetes, and inflammatory bowel disease (IBD). [234567] Vitamin D receptors have been found in the immune system, reproductive system, endocrine system, muscle, brain, skin, and liver as well as the bone, kidney, and intestine;[8] supporting the idea of the role of Vitamin D is not limited to the skeletal system.…”
Section: Introductionmentioning
confidence: 99%
“…The tolerization regimen uses a single infusion of autologous peripheral blood mononuclear cells, which are chemically coupled with seven myelin peptides (MOG 1-20 , MOG 35-55 , MBP 13-32 , MBP 83-99 , MBP 111-129 , MBP , and PLP [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154] It was demonstrated that the therapeutic effect of the amyloid-forming proteins, tau, aB crystallin, and amyloid P protein, is due to amyloidogenic peptides composed of six amino acids. Sci Transl Med 2013; 5:188ra175.…”
mentioning
confidence: 99%